Legal Protection of Marital Property through the Creation of a Marriage Contract - Andhika Rizky Pratiwi; Areta Edgina Apta Maharani; Nabila Pangesti Yudhiasti; Sahat Tua Richard Alexanderth (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Married Indonesians who have never entered into a marriage contract face conflict over the division of common property during divorce. On the other side, the Religious Courts have difficulties deciding such matter since neither party entered into a marriage contract, and thus lack authentic evidence related to the origin of the husband's and wife's property. The objective of this study is to examine the legal protection of marital property through the use of a marriage contract deed. This paper employed juridical-normative legal research. Subsequently, the object was studied qualitatively. The study's findings indicate that legal protection of assets in a marriage contract can occur only after the wedding take place. Where a marriage contract serves as a law for the parties, this is in accordance with Civil Code Article 1338. Additionally, Article 29 of the Marriage Law requires that the agreement's contents be carried out in good faith, taking into account applicable law, religion, standards of decency, and public order. Unless one of the parties breaches the marriage contract and causes harm to the other party, the court may grant compensation to the aggrieved party, which may include both demands for the agreement's execution as well as compensation.